Study on the plasticity improvement mechanism and grain refinement of AZ80 Mg alloy under cryogenic multi-directional forging - Shuchang Li; Zhuo Wang; Xi Zhao; Xiangdong Wang; Jianmin Yu (Journal of Materials Research and Technology, 2024)
The introduction of twin lamellae and dislocation interaction through Multi-directional forging (MDF) at room temperature (RT) has been reported to significantly improve the mechanical properties of Mg alloys. However, the Mg alloys typically exhibited poor plasticity at RT, making it highly susceptible to cracking. This study further enhanced the deformation capacity of AZ80 Mg alloy by adding a pre-cryogenic step before MDF. Compared to direct MDF at RT, MDF at cryogenic temperature (CT, −196 °C) further increased the alloy's deformation capacity from 0.72 (4P) to 1.08 (6P), with the tensile yield strength (TYS) and ultimate tensile strength (UTS) increasing to ∼420 MPa and ∼512 MPa. The alloy subjected to cryogenic MDF exhibited denser twin lamellae and a higher proportion of {10–12}-{10–12} twin interactions. The more frequent twin interactions under CT inhibited excessive twin growth and further increased the dislocation density of the matrix, facilitating the nucleation of new twins. Additionally, with increasing deformation passes, the texture of the RT specimens became more single, while the CT specimen showed a trend toward texture dispersion. The study elucidated that poor forgeability of the alloy under MDF at RT was hindered by unfavorable texture and limited twin activation. However, this issue was mitigated under CT, where the activation of more atypical twins with low Schmid factors (SFs) significantly enhanced the deformation coordination ability. Furthermore, the activation of atypical twins and extensive twin interactions promoted texture dispersion in CT specimens, which facilitated the activation of various slips/twins and suppressed excessive twinning-induced hardening, thereby improving forgeability.